2007
DOI: 10.1063/1.2738476
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the local composition enhancement and related dynamics in supercritical CO2-cosolvent mixtures via computer simulation: The case of ethanol in CO2

Abstract: The supercritical mixture ethanol-carbon dioxide (EtOH-CO2) with mole fraction of ethanol X(EtOH) congruent with 0.1 was investigated at 348 K, by employing the molecular dynamics simulation technique in the canonical ensemble. The local intermolecular structure of the fluid was studied in terms of the calculated appropriate pair radial distribution functions. The estimated average local coordination numbers and mole fractions around the species in the mixture reveal the existence of local composition enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 58 publications
5
44
0
Order By: Relevance
“…The simulation was performed at constant temperature and volume, corresponding to an experimentally reported sc thermodynamic state point ͑T=348 K, = 0.611 g / cm 3 ͒. 31 According to previous experimental studies the critical temperature of the mixture at this particular composition has estimated to be about 326 K, 31,36 therefore the investigated fluid mixture is at sc conditions. The intermolecular interactions are represented as pairwise additive with site-site Lennard-Jones ͑LJ͒ and Coulombic interactions.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulation was performed at constant temperature and volume, corresponding to an experimentally reported sc thermodynamic state point ͑T=348 K, = 0.611 g / cm 3 ͒. 31 According to previous experimental studies the critical temperature of the mixture at this particular composition has estimated to be about 326 K, 31,36 therefore the investigated fluid mixture is at sc conditions. The intermolecular interactions are represented as pairwise additive with site-site Lennard-Jones ͑LJ͒ and Coulombic interactions.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Although a small number of experimental and theoretical studies devoted to the properties of sc CO 2 -methanol mixed solvents ͑with X methanol ϳ 0.01-0.11͒ have been reported up to now, [18][19][20][21][22][23][24][25][26][27][28][29] studies on the properties of scCO 2 -ethanol ͑EtOH͒ systems are quite rare and most of them correspond mainly to dilute mixtures. 24,[30][31][32][33][34][35][36][37] In a quite recent study, two of the authors presented a molecular dynamics ͑MD͒ simulation study on the local intermolecular structure and related dynamics for the sc CO 2 -EtOH binary mixture at a mole fraction X ethanol ϳ 0.1. 36 The results obtained in that study have revealed a nonideal mixing behavior of the mixture and the existence of a somewhat restricted aggregation between the ethanol molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, several models of carbon dioxide have been described in the literature [14][15][16][17][18][19][20][21][22][23][24]. The three following main principles of describing molecules may be distinguished among them:…”
Section: Introductionmentioning
confidence: 99%
“…Within the framework of this approximation, three partial charges correspond to the force centers of the atoms in CO 2 . The EPM2 three point model [15][16][17][18] is most commonly used among them.…”
Section: Introductionmentioning
confidence: 99%